The Effectiveness Of Powtoon Media Based On Inquiry Learning In History Lesson Class XI SMAN 1 Panarukan - Ani Juwita; Desi Nurul Imaniah; Akalily Normalina; Puji Rizki Irani (JURNAL HISTORICA, 2022)
Competency development in the digital era is urgently needed by students as they face the challenges of 21st century education. Educators are required to innovate in teaching history in order to develop students' abilities optimally. However, the results of previous research indicate that there are problems related to learning media. The purpose of this study was to determine the effectiveness of Powtoon media based on inquiry in learning history for class XI SMAN 1 Panarukan. This type of research uses experimental research with the One Group Pretest-Posttest Design pattern. The results of the study achieved a relative effectiveness value of 69.01% in the "High Effectiveness" category. So it can be concluded that the use of Powtoon media based on Inquiry Learning has high effectiveness in class XI history at SMAN 1 Panarukan. Keywords: Effectiveness, Powtoon Media, Inquiry Learning, History Lesson